2011
DOI: 10.1137/090774112
|View full text |Cite
|
Sign up to set email alerts
|

A New Upper Bound for the Irregularity Strength of Graphs

Abstract: A weighting of the edges of a graph is called irregular if the weighted degrees of the vertices are all different. In this note we show that such a weighting is possible from the weight set {1, 2, . . . , 6 n δ } for all graphs not containing a component with exactly 2 vertices or two isolated vertices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
114
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(115 citation statements)
references
References 8 publications
0
114
0
1
Order By: Relevance
“…As we can see, it is the multiplicative version of the well known irregularity strength introduced by Chartrand et al in [5] and studied by numerous authors (the best result for general graphs can be found in Kalkowski, Karoński and Pfender [6], while e.g. trees and forests have been studied e.g.…”
Section: Introductionmentioning
confidence: 98%
“…As we can see, it is the multiplicative version of the well known irregularity strength introduced by Chartrand et al in [5] and studied by numerous authors (the best result for general graphs can be found in Kalkowski, Karoński and Pfender [6], while e.g. trees and forests have been studied e.g.…”
Section: Introductionmentioning
confidence: 98%
“…The smallest value of s that allows an irregular labeling is called the irregularity strength of G and denoted by s(G). This problem was one of the major sources of inspiration in graph theory [3,4,5,6,7,12,18,19,20,23,26,28]. For example the concept of G-irregular labeling is a generalization of irregular labeling on Abelian groups.…”
Section: Introductionmentioning
confidence: 99%
“…Namely, the authors in [17] have proved that s(G) ≤ 6 n/δ < 6n/δ + 6. Currently Majerski and Przybyło [19] proved that s(G) ≤ (4 + o(1))n/δ + 4 for graphs with minimum degree δ ≥ √ n ln n. For a given vertex labeling h : V (G) → {1, 2, .…”
Section: Introductionmentioning
confidence: 99%